The changing incidence of dengue fever in Hulu Langat, Selangor: a 5-year registry-based analysis - Ramli, Lina Farhana; Mohd Tohit, Nor Faiza; Salleh, Rosilawati; Suli, Zaliza (Malaysian Medical Association, 2019)
INTRODUCTION: Dengue fever, a mosquito-borne disease that occurs in tropical and subtropical areas of the world, is a significant threat for the mankind in both developing and developed countries. Dengue virus infection is a systemic disease and has dynamic change in clinical phase. This research aimed to study the epidemiology of dengue with reference to demographic profile, circulating serotypes and complications. METHODS: A literature survey was conducted and demographic data between 2014 and 2018 in e-Dengue registry were analysed to describe the epidemiology of dengue cases in Hulu Langat. RESULTS: The highest incidence rate, 254.3 per 100,000 populations was recorded in 2015 (n=14,939). Urban sub-districts (88.3%), male (57%), Malay (61.5%), age group 18-40 years old (51%) and landed house (61%) contributed most of the cases. Case-fatality rate increased from 2014 to 2017 (0.0018 to 0.0022) but decreased in 2018 (0.0014). Out of 114 mortalities, majority were male (53%), age 18-40 years old (46%) and Malay (63%). Complications recorded were liver failure (60%), renal failure (51%), encephalitis (18%) and myocarditis (18%). In year 2014- 2015, DEN-1 serotype was dominantly reported (52.2% and 56.5%), shifted to DEN-3 in year 2016-2017 (34.8% and 43.4%) and DEN-2 in year 2018 (49.5%). DISCUSSION: Hulu Langat, being hyperendemic, the occurrence of multiple organ involvement following dengue infections has become a frequent finding. The study emphasizes the need of epidemiological and entomological surveillance to monitor trends in dengue distribution, seasonal patterns and circulating serotypes to guide dengue control activities, especially in rapidly growing urban and suburban areas.